Pengendalian Kualitas Produk Kayak dengan Menggunakan Metode PDCA (Plan Do Check Action) dan FMEA (Failure Mode and Effect Analysis) di PT Ongpin Jaya Indonesia - Iyan Bachtiar; Mega Widya Lestari; Dewi Shofi Mulyati (Bandung Conference Series: Industrial Engineering Science, 2023)
Abstrack. PT Ongpin Jaya Indonesia is a company engaged in the manufacturing sector in Indonesia and focuses on manufacturing kayak products. During the kayak boat production process there is a discrepancy in terms of completion of production. One of the obstacles to the occurrence of defects caused by human error factors that result in products not in accordance with the company's needs. The purpose of this study was to reduce product defects in kayak boats using the plan-do-check-action and failure mode effect and analysis methods. The plan stage is carried out to find the most dominant type of defect and find the root cause of the defective product using a Pareto diagram. Based on the Pareto diagram, the research focuses on repairing 1 type of defect, namely the type of asymmetrical shape defect, the factors causing the defect using a Fishbone diagram. Stage do After knowing the cause of the defect, determine goals and objectives in corrective action and identification of defective products and assisted by tools 5W + 1H. In the check phase, further examination was carried out using failure mode effect and analysis, and the highest risk priority number was obtained, namely 324 at the temperature of the injection molding machine where setting errors often occur, and the recommended action was given in the form of a proposal to make a special checksheet for engine temperature control. The next stage is the action stage, as well as looking at the quality level of a product by using a checksheet to review the inspection process. Abstrak. PT Ongpin Jaya Indonesia merupakan perusahaan yang bergerak di bidang manufaktur di Indonesia dan berfokus kepada pembuatan produk perahu kayak. Selama proses produksi perahu kayak terdapat ketidaksesuaian dalam hal penyelesaian produksi. Salah satu kendala terjadinya cacat yang disebabkan oleh faktor human error yang mengakibatkan produk tidak sesuai dengan kebutuhan perusahaan. Tujuan penelitian ini adalah untuk mengurangi produk cacat pada produk perahu kayak di menggukan metode plan-do-check-action dan failure mode effect and analysis. Tahap plan dilakukan untuk mencari jenis defect yang paling dominan dan mencari akar penyebab terjadinya produk yang cacat menggunakan diagram pareto. Berdasarkan diagram pareto, penelitian fokus memperbaiki 1 jenis defect yaitu jenis defect bentuk tidak simetris, faktor-faktor penyebab defect tersebut menggunakan Fishbone diagram. Tahap do Setelah diketahui penyebab terjadinya defect, Menentukan sasaran dan tujuan dalam tindakan perbaikan dan identifikasi produk cacat dan dibantu oleh tools 5W+1H. Tahap check dilakukan pemeriksaan lebih lanjut dengan menggunakan failure mode effect and analysis, dan didapatlah nilai risk priority number yang paling tinggi yaitu sebesar 324 pada temperatur suhu mesin injection molding yang sering terjadi kesalahan setting, dan recommended action yang diberikan berupa usulan untuk pembuatan checksheet khusus untuk pengontrolan suhu mesin. Tahap selanjutnya adalah tahap action, serta melihat tingkat kualitas suatu produk dengan menggunakan checksheet untuk meninjau pada proses pemeriksaan.